Epoxy Isonitriles, A Unique Class of Antibiotics: Synthesis of Their Metabolites and Biological Investigations. (31st October 2018) - Ernouf, Guillaume; Wilt, Ingrid K.; Zahim, Sara; Wuest, William M.
Abstract: Epoxy isonitrile containing natural products often possess specific and potent antibacterial activity against Gram‐positive pathogens. This scaffold, however, is extremely labile under acidic and basic conditions, undergoing a Payne rearrangement to produce a stable epoxy ketone metabolite and releasing hydrogen cyanide. We synthesized and performed biological assays with epoxy ketone containing metabolites and identified that the epoxy isonitrile moiety is pertinent for biological activity. Serendipitously, we discovered an α, β‐unsaturated epoxy ketone analogue that exhibited moderate activity against Staphylococcus aureus . Abstract : Made to order : Epoxy isonitrile containing natural products often possess specific and potent antibacterial activity against Gram‐positive pathogens. This scaffold, however, is extremely labile under acidic and basic conditions, undergoing a Payne rearrangement to produce a stable epoxy ketone metabolite. We synthesized and performed biological assays with epoxy ketone containing metabolites and identified that the epoxy isonitrile moiety is pertinent for biological activity.